The instructional design of a virtual reality (VR)-based car maintenance learning system - Tan, S.C.; Chen, Chwen Jen; Mohammad, N.A. (2007)
This paper reports the instructional design of a virtual reality (VR)-based learning system, which is meant for car drivers to learn about basic car maintenance procedures. The instructional design model proposed by Chen, Toh and Fauzy (2004) was chosen to guide the design of this learning system as this model is derived specifically to guide the design of VR based learning environments. In brief, the model comprises two main strategies, the macrostrategy that concerns with the selection, sequence, and organisation of the subject matter topics that are to be presented, and the micro-strategy that proposes a number of design principles for effective presentation of learning materials. This paper provides a detail description of how the VR-based car maintenance learning system was designed in line with these strategies.